Altered neural function during episodic memory encoding and retrieval in major depression. Issue 9 (17th March 2014) - Dietsche, Bruno; Backes, Heidelore; Stratmann, Mirjam; Konrad, Carsten; Kircher, Tilo; Krug, Axel
Abstract Memory impairments are common in major depression. Neural processing during non‐emotional episodic memory in depressed patients has only sparsely been investigated, since the majority of studies have focused on emotional stimuli. The aim of this study was to explore neural correlates of episodic memory in depressive patients and to assess brain regions related to subsequent memory performance. Forty‐six participants (23 depressed patients) performed a non‐emotional episodic memory encoding and retrieval task while brain activation was measured with functional magnetic resonance imaging. Patients with depression showed decreased activation in the right prefrontal cortex and right cingulate cortex during memory encoding, but increased activation in the right inferior frontal gyrus (IFG) during recognition memory. While a strong association between hippocampal and parahippocampal activation during memory encoding with subsequent memory performance became evident in healthy controls, this relationship was absent in patients with depression. Taken together, these findings demonstrate that memory related brain regions are affected in their appropriate functioning during memory encoding in depressed patients. Therefore, patients with depression may rely to a greater degree on other brain regions such as the IFG during episodic memory retrieval. Hum Brain Mapp 35:4293–4302, 2014. © 2014 Wiley Periodicals, Inc.